An Ordinance Relating to the Carrying of Fire Arms and Other Deadly Weapons, in THE ABILENE CHRONICLE, May 12, 1870, at 1, § 3 - (:unkn) unknown (My University, 1870)
§ 3: Prohibited intentionally discharging any pistol, revolver, or gun in any street, alley, highway, lot, house, or other place where life or limb could be endangered. Violators fined not less than ten dollars nor more than one hundred dollars.
Keywords: DISCHARGE